High-throughput study of the effect of indium on the microstructure and properties of copper alloy - Jiaoyan Dai; Chengpeng Liu; Shuaiqi Fan; Xiang-Xi Ye (Journal of Materials Research and Technology, 2023)
In this work, the high throughput sample of Cu-xIn (x = 0–5 wt.%) alloy was prepared by the spark plasma sintering. The effects of In content on the microstructure and properties of Cu alloys were investigated using advanced characterization. The results show that the concentration of In element linearly distributes in Cu alloy after annealing treatment at 450 °C. Most In elements exist in the Cu matrix as the solid solution atoms. Some In elements are precipitated at the grain boundaries as Cu9In4 particles when the In content is higher. The hardness of the alloy increases, while the conductivity decreases with the increase of In content, which is due to the hindrance of the movement of dislocations and electrons by solid solution atoms, grain boundaries, and Cu9In4 particles. The investigation of high throughput samples can provide data support for high strength and high conductivity Cu alloys.